PERSPEKTIF GENDER DALAM PENGAMBILAN KEBIJAKAN (STUDI KASUS DI DPRD PROVINSI MALUKU PERIODE 2004 â 2009) - , LINDA PUTRI JUITA WALIULU, SE ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Gender is a specific issue that related with a big group in society, that is women. At the period of 2004 â 2009, Maluku Regional House of Representative was never validated the regional rule or policy that connected with gender because at that moment they were concentrated more on infrastructure and postâconflict development. Related with that problem, this research has an aim to reveal and inform descriptively about how good is legislative ability in accommodate gender problems and the factors that influence it. In this research, the writer using descriptive research method and qualitative approach. Data informants are consists of: Head and Head Representative of Maluku Regional House of Representative, Member of Maluku Regional House of Representative, Former Member of Maluku Regional House of Representative, Governmentâs Official in connection with this matter, public figure, and activist. Result of the research shows that the capability of legislative member in accommodated rules that based on gender at Maluku Regional House of Representative committee during 2004 â 2009 was still very low. From so many regional rules that had been created by Maluku Regional House of Representative at that time, never ever known there was a regulation that concerning about the importance of gender. Some cases that caused this problem were: First, Member of Maluku Regional House of Representativeâs orientation towards their duty and right as legislative member, Second, there was no supporting condition to force Maluku Regional House of Representative for accommodate womenâs necessity, and Third, there was no politic power which was equal with Maluku Regional House of Representative because executive committee also had different paradigm towards gender. The ability of government and legislative in drafting legal still very low because of law instrument that still not suffice enough and the culture or behavior that still characterized by the new government era in Indonesia. The capability and comprehension in politic, education and politic importance are valued as rather important obstacle. If the policy cannot be seen yet significantly, Regional House of Representativeâs ability and its understanding towards public politic education also need to be questioned. Besides that, government as the executive side shall to possess the commitment, capability and comprehension to politic education, so that group of gender can be more developed to become a group that has control power towards their own necessity.